The Effect of Thermal Activation Time and Different Curing Condition On Bamboo Ash - Andi Dibya Widadi (International Association of Lowland Technology, 2019)
At the time of the execution of the construction project are frequent discrepancies between a sign and a schedule of realization in the field that can lead to an implementation time and swelling she cost so that the actions of the project becomes obstructed. The delay in the implementation of the construction project could be addressed by conducting acceleration in its implementation in order to achieve the targets of the plan. However in decision-making to accelerate the implementation of the work certainly should pay attention to factors of financing so that the expected results are valid minimal cost without neglecting the quality standards that you want. One method of acceleration duration that can be used this way is a method of exchanging time and costs or time cost trade off. The purpose of this method is to speed up the implementation of the project and analyze the effect of time can be shortened by the addition of costs so as to note the most maximum acceleration and the most minimal. The calculation starts with the search for critical path and then going to get charged slammed into do the slopes. Next suppressor duration starts from the activity that has the lowest cost. From the results of both the addition of overtime hours, the addition of 4 (four) hours of overtime are more advantageous in terms of costs and time because the total cost of the guardian only happens in relatively small amounts and the resulting time efficiency is higher than additions to the 7 (seven) overtime hours.